2007
DOI: 10.1111/j.1600-065x.2007.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of β‐chemokines in mast cell activation and type I hypersensitivity reactions in the conjunctiva: in vivo and in vitro studies

Abstract: Chemokines have a clearly defined role in mobilizing the recruitment of leukocytes to both healthy and inflamed tissues. This review details work from our and other laboratories, indicating that beta-chemokines may play important roles (i) in driving the terminal differentiation of mast cell precursors in mucosal tissues and (ii) in providing priming or costimulatory signals required for mast cell activation, leading to an antigen-driven inflammatory response. These data stem from in vivo, ex vivo, and in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Of importance, CCR2 is also expressed on mature mast cells. 15 Because mast cell activation is pivotal in the pathophysiology of allergic conjunctivitis, we performed in vivo experiments to test whether MCP-1 can activate conjunctival mast cells. Recombinant MCP-1 was injected beneath the conjunctiva of naive mice.…”
Section: Effects Of Mcp-1 Injection On Conjunctival Eosinophils and Mmentioning
confidence: 99%
“…Of importance, CCR2 is also expressed on mature mast cells. 15 Because mast cell activation is pivotal in the pathophysiology of allergic conjunctivitis, we performed in vivo experiments to test whether MCP-1 can activate conjunctival mast cells. Recombinant MCP-1 was injected beneath the conjunctiva of naive mice.…”
Section: Effects Of Mcp-1 Injection On Conjunctival Eosinophils and Mmentioning
confidence: 99%
“…Besides the classical Fc⑀RI-mediated mechanism, mast cells are also activated by chemokines (3,4). A superfamily of small, structurally related cytokine molecules, chemokines are characterized by their ability to affect trafficking of leukocytes.…”
mentioning
confidence: 99%
“…A superfamily of small, structurally related cytokine molecules, chemokines are characterized by their ability to affect trafficking of leukocytes. Some chemokines, such as CCL2/MCP-1 (monocyte chemotactic protein 1), CCL3/MIP-1␣ (macrophage inflammatory protein-1␣), CCL5/RANTES (regulated upon activation, normal T-cell expressed and secreted), and CCL11/eotaxin-1, have been reported to activate mouse, rat, or human mast cells (3)(4)(5)(6). Abundant expression of these CC chemokines and accumulation of leukocytes has also been observed in allergic inflammatory tissues (7)(8)(9).…”
mentioning
confidence: 99%
“…Rat basophilic leukemia (RBL)-2H3 cells expressing human CCR1 (RBL-CCR1 cells) (Richardson et al, 2000) were used in this study, as they have previously been shown to display greater mast cell activity than the parental cell line (Beer et al, 2007;Toda et al, 2004). Chemokine receptor 1 (CCR1) is expressed by mast cells, (Miyazaki et al, 2005) and its ligand CC chemokine ligand 3 (CCL3), also known as macrophage inflammatory protein 1α (MIP-1α) stimulates mast cell degranulation (Alam et al, 1992;Miyazaki et al, 2005).…”
Section: Introductionmentioning
confidence: 99%